Thieme atlas of anatomy : head and neuroanatomy - Schuenke, Michael; Schulte, Erik; Schumaker, Udo; VOLL, MARKUS; WESKER, KARL (United State of America : Thieme, 2010)
With teh Thieme Atlas of Anatomy, it was our intention to create an altas that would guide students in their initial study of anatomy, stimulate their enthusiasm for this intriguing and vitally important subject, and provide a reliable reference for experienced students and povide a reliable reference for experienced students and professionals alike.
Part I: Head 1. Cranial bones 2. Muscles of the head 3. Blood vessels of the head and neck 4. Cranial nerves 5. Topographical anatomy and others...
Includes bibliographical references
Includes index
Keywords: FUNCTIONAL NEUROANATOMY; CENTRAL NERVOUS SYSTEM -- ATLAS; NEUROANATOMY -- ATLAS